2016
DOI: 10.3349/ymj.2016.57.3.776
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Acoustic Neuroma: Systematic Review and Meta-Analysis

Abstract: PurposeMany epidemiological studies have investigated environmental risk factors for the development of acoustic neuroma. However, these results are controversial. We conducted a meta-analysis of case-control studies to identify any potential relationship between history of noise exposure, smoking, allergic diseases, and risk of acoustic neuroma.Materials and MethodsWe searched PubMed to identify relevant articles. Two researchers evaluated the eligibility and extracted the data independently.ResultsEleven cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
0
24
0
2
Order By: Relevance
“…Acoustic neuromas are the most common type of tumor in the region of the internal auditory canal with a higher prevalence in females than in males [3] . Our study found the same trend, with a larger prevalence of ANs in women (n = 59.1%) than in men (n = 40.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic neuromas are the most common type of tumor in the region of the internal auditory canal with a higher prevalence in females than in males [3] . Our study found the same trend, with a larger prevalence of ANs in women (n = 59.1%) than in men (n = 40.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic neuromas (ANs), or vestibular schwannomas, which were first identified in 1777 by Eduard Sandifort [1] , represent a type of benign brain tumor of Schwann cells that mostly arises from the vestibular nerve [2] . ANs represent one of the most common intracranial tumors with an incidence from 1 to 20 per million, and ANs accounts for approximately 6% of all intracranial tumors [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Porém, já existem estudos que associam a forma esporádica com exposição à radiação e exposição ocupacional aofumo de tabaco e mercúrio 3 . Não há relação significativa entre o SV e os processos alérgicos, uso de drogas anti-histamínicas, traumatismo craniano, trauma acústico ou outras doenças neoplásicas 7 .…”
Section: Descritores: Schwannoma Vestibular; Epidemiologia;unclassified
“…For the unilateral presentation, the median age at diagnosis is 50 years, with a gender ratio (F:M) greater than 1. A bilateral vestibular schwannoma is pathognomonic of neurofibromatosis type 2 (NF2) and occurs in younger age, typically at 10-20 years (Chen et al 2016).…”
Section: Epidemiologymentioning
confidence: 99%
“…-Childhood exposure to ionizing radiation due to medical treatment or extraordinary events (i. e., atomic explosions) (Schneider et al 2008); -Exposure to electromagnetic fields; a recent meta-analysis reported a significantly higher risk for any type of intracranial tumor after use of mobile phone over 10 years (odds ratio (OR) = 1.3, 95% confidence interval (CI): 1.028-1.704) (Bortkiewicz et al 2017); -Noise exposure; a meta-analysis published in 2016 suggests an elevated risk for acoustic neuroma in individuals who were ever exposed to leisure noise (OR = 1.3, 95%CI: 1.05-1.68), but not to occupational noise (OR = 1.2, 95% CI: 0.84-1.72) (Chen et al 2016).…”
Section: Epidemiologymentioning
confidence: 99%